Sustainability integration into engineering curricula within five research universities in Malaysia / Chiong Kai Shing - Chiong, Kai Shing (2015)
Sustainability or sustainable development has become a recent focus in industries and education. Tertiary education, especially engineering education plays an irreplaceable role in sustainability education in view of the active roles played by engineers in steering technology development. There is however, limited information on the relationship between sustainability integration into formal, informal and non-formal engineering curricula with engineering undergraduates’ knowledge and interest on sustainability in Malaysia. Therefore, this study aims at identifying the current integration strategy used by the Malaysian Institutions of Higher Education (IHEs) in integrating sustainability into the formal engineering curricula of four traditional engineering disciplines, which are Chemical, Civil, Mechanical and Electrical Engineering and identifying the response of the respective engineering students to such integration strategies through evaluating students’ knowledge and interest in sustainability. Besides, this study also aims at proposing a possible sustainability integration strategy for the respective engineering discipline by combining formal, nonformal and informal curricular approach with an additional discussion on whether vertical (stand-alone or specific subjects on sustainability) or horizontal approach (intertwine of sustainability components into the existing subjects) is more suitable for an engineering discipline in Malaysia based on the proposed strategy. Curricular analyses were conducted in this study to identify the current integration strategy while a questionnaire was the main research instrument for measuring students’ knowledge and interest in sustainability and collecting data for developing the possible integration strategy for sustainability integration in each engineering discipline. Statistical Packages for Social Science (SPSS) were used for analytical purposes. A total of 871 questionnaires were collected from the four engineering disciplines from five researchbased IHEs in Malaysia which have the most established history in offering the iv respective engineering programmes compared to the other IHEs in Malaysia. The curricular analyses revealed that 87% and 92% of the sustainability related courses for Chemical and Civil Engineering, respectively were of the horizontal approach while 100% of the sustainability related courses for Mechanical and Electrical Engineering were of the horizontal approach. The analyses showed that generally, the engineering students had moderately high to high knowledge and interest level in sustainability with the Civil Engineering students having the highest score. For the possible sustainability integration strategy, further analyses showed that the integration strategy varied with engineering disciplines and it was found that the vertical approach was preferred for Chemical and Civil Engineering while the horizontal approach was preferred for Mechanical and Electrical Engineering. The secondary finding from the questionnaire revealed that peer influence was among the main motivating factors for students’ participation in sustainability activities. In summary, the study showed that the current strategy used by the IHEs for sustainability integration into engineering education had yielded some satisfactory results by cultivating certain intellectual or interest level among the engineering students in Malaysia towards sustainability, but there are rooms for improvement, as detailed in the thesis. This study successfully developed a possible sustainability integration strategy for each of the targeted engineering disciplines in this study to further improve the effectiveness of sustainability education for the Malaysian engineering students.